Parental Involvement in Academic Performance of Girl Child in Primary Schools in Buseta Sub-County of Kibuku District, Uganda - Muguli, Micheal; Turyahabwe, Deneth; Tukur, Muhammad; Bagiwa, Zulaihat L.; Turyamureeba, Silaji (Newport International Journal of Current Research in Humanities and Social Sciences, 2024)
The study examined parental participation and girl-child academic achievement in elementary schools in Buseta Sub County, Kibuku District. Cross-sectional survey research design was used for the study and data were collected via questionnaires. The findings showed that numerous socio-economic factors affected parental involvement in girl-child education in Buseta Sub County elementary schools including social class, income, parents' attitudes towards girl-child education, cultural norms, parental education, inadequate government policy, and school distance were among these factors. Based on the findings, the study calls for parents and guardians should be educated on the benefits of lowering girls’ workload at home. Furthermore, private primary schools should offer scholarships to underprivileged girls. Since parents are stakeholders in the girl child's education, School Management Committees should educate them on their roles. Parents and guardians should schedule time to help their children, especially girls, access school resources. Finally, the government should provide energy and subsidise solar power projects in rural areas to assist children in finishing their homework with parents/guardians.